The Middle Ages, Church, and Science (From the History of Atheistic Thought in Lithuania: The Late 19th and the Early 20th Centuries) - Barzdaltis, Juozas (Problemos, 1973)
The article discusses the views of Lithuanian atheists of the late 19th and the early 20th centuries on the Medieval Church and the harm done by it lo the development of science. It emphasizes the harm caused by blind fanaticism when the emotional aspect of revering supernatural powers was considered to be first and foremost, when faith, not knowledge, was the only requirement for man’s salvation, while the human thought was bound by scholasticism and dogmata.